Kewajiban Mempekerjakan Penyandang Disabilitas Pada Perusahaan Badan Usaha Milik Negara dan Perusahaan Swasta Di Kabupaten Tebo - Yudhistira, Lily; Raffles, Raffles; Windarto, Windarto (Zaaken: Journal of Civil and Business Law, 2024)
The purpose of writing this thesis is to know and analyze how the fulfillment of labor rights for people with disabilities in state-owned companies and private companies in Tebo Regency, as well as to find out and analyzeobstacles in fulfilling labor rights for people with disabilities in Tebo Regency. The method in writing this research uses empirical juridical research methods that focus research on reality or legal behavior in society by examining the gap between Das Sollen and Das Sein, namely by realizing the application of Law Number 8 of 2016 concerning Persons with Disabilities in Tebo Regency. The results of this study show that 1) the fulfillment of labor rights for people with disabilities in state-owned and private companies in Tebo Regency is said to be rudimentary 2) the obstacles that make the non-fulfillment of labor rights for people with disabilities are because many companies do not have awareness of labor rights for people with disabilities , people with disabilities get jobs Based on the level of disability, the lack of self-confidence possessed by people with disabilities, the mindset of people with disabilities who consider that the shortcomings they have are a disgrace, and because the criteria desired by the company cause indirect discrimination attitudes for people with disabilities, and the average education of people with disabilities is still low.